Awareness and Perception of Certified Librarians of Nigeria Towards the Use of Robotic Technologies in the Libraries - Saliu Sambo, Atanda; Oyovwe-Tinuoye, Gloria (Ghana Library Journal, 2023)
The study adopted the social survey technique and the population of the study comprised 452 certified librarians of Nigeria libraries that were certified by the Librarians’ Registration Council of Nigeria (LRCN) on November, 24th, 2021. The librarians who took part in the survey were chosen using a random sampling method. One out of every three librarians being admitted on the day was given the questionnaire. The researcher used Statistical Package for the Social Sciences (SPSS version 20.0) application software with simple percentages chosen for easier analysis and interpretation. The findings of this study revealed that certified librarians are averagely aware of the existence of robotic technologies usage for library services and the anxiety of employee retrenchment is the major anxiety, despite they are aware that, the innovative apparatuses will increase global recognition and enhance library services. It shows that certified librarians are faced challenges towards the use of robotic technologies such as potential job loss, inadequate funding and epileptic among others. The study recommended that certified librarians should keep up with modern trends in information dissemination by learning fundamental skills that are technologically compatible among others.